Preeclampsia and Preterm Delivery Risk: The Significance of Obesity in Pregnancy - Tamara Perić; Mirjana Bogavac; Zoran Belopavlović (Биомедицинска истраживања, 2024)
Introduction: A significant proportion of women globally, consti tuting 38%, are obese, among whom 24.5% reside in Europe. Obe sity elevates the risk of premature birth due to associated maternal conditions, such as preeclampsia. The objectives were to assess: variations in demographic and clinical characteristics among preg nant women across groups; the impact of obesity on the incidence of preeclampsia and preterm delivery; and the influence of obesity on newborn characteristics. Methods: One-year prospective study included 133 pregnant wom en gestational age 11-14 gestational week (GW), divided into two groups: OB (41.35%) and CG (58.65%). The data were analyzed using IBM SPSS version 23. Results: There is statistically significant difference in average body mass index (BMI) (22.01 ± 1.83 vs. 30.26 ± 4.52; p < 0.001) and de livery time (37.94 ± 2.05 vs. 36.87 ± 2.45; p = 0.003) between CG and OB. Obese pregnant women developed preeclampsia significantly more often than normal weight (61.82% vs. 28.21%; p < 0.001). Body mass index has significant moderate predictive ability to predict preeclampsia (AUC 0.696 (95% CI: [0.601; 0.79]). Higher BMI (OR = 1.19, [1.09; 1.29], p < 0.0001) was associated with higher rates of pre eclampsia. Overweight (OR = 2.41, [1.07; 5.43], p = 0.0335), obesity class I, II and III (OR = 20.36, [4.32; 95.99], p = 0.0001) were associated with higher rates of preeclampsia. A poor negative correlation was found between BMI and GW of pregnancy outcome (p = -0.24; r2 = 0.104; p = 0.006). Higher BMI (? = -0.14, [-0.21; -0.07], p = 0.0002) was associated with lower values of GW of pregnancy outcome. Conclusions: Presence of obesity or overweightness in the first tri mester of pregnancy poses a significant risk factor for preeclampsia and preterm delivery.
Keywords: obesity in pregnancy; preeclampsia; preterm delivery